The codex sacromontanus of Alexander’s "Commentary on «Metaphysics»": Textual Filiation - Gatsioufa, Paraskevi (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
In this article the textual fi liation of the greek codex sacromontanus, which transmits the Commentary of Alexander on «Metaphysics», has been investigated for the fi rst time. It has been achieved to establish its stemmatic relationships with other manuscripts as well as to determine and confi rm its text-critical value.